Selection of peptide inhibitors of interactions involved in complex protein assemblies: association of the core and surface antigens of hepatitis B virus. - Dyson, M R (1995)
As an example for studies of contacts involved in complex biological systems, peptide ligands that bind to the core antigen of hepatitis B virus (HBcAg) have been selected from a random hexapeptide library displayed on filamentous phage. Affinity-purified phage bearing aa sequence LLGRMK, or some related sequences, bound full-length or truncated HBcAg but did not bind denatured HBcAg. The long (L), but not the short (S), hepatitis B virus envelope polypeptide, when synthesized in an in vitro system, bound firmly to HBcAg, indicating that interaction between HBcAg and the pre-S region of the L polypeptide is critical for virus morphogenesis. This interaction was inhibited by peptide ALLGRMKG, suggesting that this and related small molecules may inhibit viral assembly.